Options for surgical treatment of cervical fractures in patients with spondylotic spine: a case series and review of the literature. (December 2015) - Alves, Pedro; Martins, Delio; Ueta, Renato; Del Curto, David; Wajchenberg, Marcelo; Puertas, Eduardo
Abstract Introduction The surgical treatment of unstable cervical fractures is challenging for spinal surgeons. Unstable cervical fractures associated with spondyloarthropathy and deformities that alter function, form and stability present a greater challenge. Having multiple options to manage this difficult situation is important to all spine surgeons and the results of each case depends on the singular characteristics of patients. The purpose of this case report is to describe the main forms of presentation of unstable cervical subaxial fractures in the spondylotic spine and their surgical treatments. Case presentation We present three cases of Caucasian men aged 30, 53 and 59 years with spondylosis with unstable cervical fractures and alternatives choices for surgical treatment, and a review of the literature. Each patient underwent a different surgical procedure of the cervical subaxial spine using an isolated anterior, posterior or combined approach demonstrating good outcomes in all cases. Conclusions The treatment of subaxial cervical spinal fractures is complex, and when these fractures are associated with the deformities caused by spondyloarthropathies they can be thought provoking for spine surgeons such as orthopedists or neurosurgeons. The isolated anterior, posterior and combined approaches are safe and effective for treating these pathologies.